Total cholesterol, high-density lipoprotein, and glucose (CHG) index and diabetic retinopathy in middle-aged and elderly Chinese adults with diabetes: a cross-sectional study - Cao, Yingpin; He, Yuqin; Zhu, Jiaqian; Han, Yong (Frontiers in Endocrinology, 2026)
ObjectiveEvidence regarding the association between the total cholesterol, high-density lipoprotein, and glucose (CHG) index and diabetic retinopathy (DR) remains limited. This study aimed to explore the relationship between CHG and the prevalence of DR and evaluate its discriminative ability for DR.MethodsThis cross-sectional study analyzed data from 1,909 individuals with diabetes mellitus (DM), aged 45–90 years, whose information was collected between August and December 2011. To determine the association between CHG and DR, binary logistic regression models were employed. The discriminative ability of CHG for DR was assessed using receiver operating characteristic (ROC) analysis. Additionally, a series of sensitivity analyses and subgroup analyses were conducted.ResultsAfter multivariable adjustment, binary logistic regression analysis showed that each 0.1−unit increase in CHG was associated with a 14.2% higher prevalence of DR (OR = 1.142; 95% CI: 1.081–1.206). Additionally, CHG demonstrated the highest area under the curve (AUC) for discriminating DR (0.6673, 95% CI: 0.6287–0.7059), outperforming triglyceride-glucose body mass index (TyG-BMI, 0.4958, 95% CI: 0.4548–0.5368), triglyceride to high-density lipoprotein cholesterol ratio (THR, 0.5118, 95% CI: 0.4704–0.5532), and triglyceride-glucose index (TyG, 0.5720, 95% CI: 0.5314–0.6125). Sensitivity analysis and subgroup analyses further confirmed the reliability of these results.ConclusionThis study demonstrates that elevated CHG is independently and positively associated with DR in adults with DM. Moreover, CHG shows a certain discriminative ability for DR and may have potential utility in DR assessment.